1974
DOI: 10.1079/bjn19740109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and inorganic sulphur on the availability of dietary copper to sheep

Abstract: I . The effects of dietary sulphur on the availability of dietary copper were estimated by means of a repletion technique. The responses of initially hypocupraemic ewes to repletion with Cu-supplemented diets containing supplements of organic S, as methionine, and of inorganic S, as Na,SO,, were compared with those obtained with a diet low in S.2. The two forms of S had similar effects. Responses in plasma Cu were reduced by 3 9 3 6 % when S was increased from 1.0 to 3.0 or 4.0 g/kg diet and the availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1
6

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 16 publications
1
60
1
6
Order By: Relevance
“…Similar results were previously observed by [72] who found a 39% -56% reduction in Cu bioavailability when S was provided to ewes as methionine or as NaSO 4 under low Mo dietary levels, possibly through the formation of insoluble CuS at sites beyond the rumen. However, [83] postulates that the formation of insoluble CuS and Cu 2 S in the rumen is exacerbated by the digestion of insoluble proteins by protozoa, with the consequent increase in available S. Despite the effect of dietary S previously mentioned, other S sources have been also responsible for decreasing Cu bioavailability in ruminants.…”
Section: Copper-sulfur Interactionsupporting
confidence: 78%
“…Similar results were previously observed by [72] who found a 39% -56% reduction in Cu bioavailability when S was provided to ewes as methionine or as NaSO 4 under low Mo dietary levels, possibly through the formation of insoluble CuS at sites beyond the rumen. However, [83] postulates that the formation of insoluble CuS and Cu 2 S in the rumen is exacerbated by the digestion of insoluble proteins by protozoa, with the consequent increase in available S. Despite the effect of dietary S previously mentioned, other S sources have been also responsible for decreasing Cu bioavailability in ruminants.…”
Section: Copper-sulfur Interactionsupporting
confidence: 78%
“…In addition, when combined with supplements of S and Mo, bentonite might bind the S and Mo supplements in the rumen and decrease their effectiveness in reducing the bioavailability of dietary copper (Ivan et al, 1999). Therefore, the remaining dietary supplements that reduce the dietary Cu bioavailability are Mo, S, Zn and Fe (Dick, 1954;Ross, 1966 and1970;Hogan et al, 1968;Suttle, 1974 and1975;Bremner et al, 1976;Phillipo et al, 1987). Owing to the fact that the concentration of Fe in PKC is known to range between 800 and 6000 mg/kg DM and was 1512 mg/kg DM in the presently used PKC, and that the excessive dietary concentrations of Fe may result in bent legs of lambs (Hidiroglou et al, 1978) and in decreased productivity in dairy cows (Coup and Campbell, 1964), the use of dietary Fe to reduce the bioavailability of dietary Cu was not considered in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that dietary Mo in the presence of an adequate S can reduce considerably the concentration of Cu in the liver (Dick, 1954;Suttle, 1974) or Cu storage in the liver (Ross 1966 and1970;Hogan et al, 1968), and that both organic and inorganic S could directly affect the absorption of dietary Cu, but to a limited degree only (Suttle, 1974 and1975), has been established decades ago. The results of the present experiment show that in comparison with the dietary Zn and Mo supplements, the combination of dietary S and Mo appears to be the best solution to control excessive dietary Cu absorption and tissue accumulation in sheep fed PKC-based diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kubota et al' (19S7) reported that primary Cu deficiencies have rarely been observed under field conditions in the United States' Sulfur can also reduce the availability of Cu in ruminants by its interaction with Mo (NRC 1984). In the rumen of catttl, l'to and S combine to form thiomolybdates, which can absorb and combine with Cu to hold it in a biologically unavailable form (Thompson et al l99l)' Suttle (1974) reported that the availability ratio of dietary Cu in sheep decreased from 0.062 to 0.041 when S was increased from I .0 to 3.0 or 4.0 g kgl . Since the range of our S values was from 0.7 to 14.0 g kg-l ltaUte 2), and 20%o of our S values exceeded the maximum tolerable level for cattle (Table 4) Iron levels were less than the minimum requlrement at only lo/o of the sites, and are consistent with previous stud_ ies in Western Canada that generally report adequate levels of Fe for ruminant nutrition (Miltmore et al 1970;Owen et al 1977;Redshaw et al 1978;Drysdale et al l9g0;Boila et al 1985).…”
mentioning
confidence: 99%